Polar Flagella Glycosylation in Aeromonas: Genomic Characterization and Involvement of a Specific Glycosyltransferase (Fgi-1) in Heterogeneous Flagella Glycosylation - Forn-Cuní, Gabriel; Fulton, Kelly M.; Smith, Jeffrey C.; Twine, Susan M.; Mendoza-Barberà, Elena; Tomás, Juan M.; Merino, Susana (Frontiers in Microbiology, 2021)
Polar flagella from mesophilic Aeromonas strains have previously been shown to be modified with a range of glycans. Mass spectrometry studies of purified polar flagellins suggested the glycan typically includes a putative pseudaminic acid like derivative; while some strains are modified with this single monosaccharide, others modified with a heterologous glycan. In the current study, we demonstrate that genes involved in polar flagella glycosylation are clustered in highly polymorphic genomic islands flanked by pseudaminic acid biosynthetic genes (pse). Bioinformatic analysis of mesophilic Aeromonas genomes identified three types of polar flagella glycosylation islands (FGIs), denoted Group I, II and III. FGI Groups I and III are small genomic islands present in Aeromonas strains with flagellins modified with a single monosaccharide pseudaminic acid derivative. Group II were large genomic islands, present in strains found to modify polar flagellins with heterogeneous glycan moieties. Group II, in addition to pse genes, contained numerous glycosyltransferases and other biosynthetic enzymes. All Group II strains shared a common glycosyltransferase downstream of luxC that we named flagella glycosylation island 1, fgi-1, in A. piscicola AH-3. We demonstrate that Fgi-1 transfers the first sugar of the heterogeneous glycan to the pseudaminic acid derivative linked to polar flagellins and could be used as marker for polysaccharidic glycosylation of Aeromonas polar flagella.